2021
DOI: 10.3390/cells10102679
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in the Onset of Schizophrenia

Abstract: Mounting evidence implicates microRNAs (miRNAs) in the pathology of schizophrenia. These small noncoding RNAs bind to mRNAs containing complementary sequences and promote their degradation and/or inhibit protein synthesis. A single miRNA may have hundreds of targets, and miRNA targets are overrepresented among schizophrenia-risk genes. Although schizophrenia is a neurodevelopmental disorder, symptoms usually do not appear until adolescence, and most patients do not receive a schizophrenia diagnosis until late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 314 publications
(424 reference statements)
2
24
0
Order By: Relevance
“…Idiopathic schizophrenia is also strongly linked to miRNAs. Most notably, genetic variants of MIR137, which encode miR-137, contribute to schizophrenia risk (Ripke et al, 2011(Ripke et al, , 2013(Ripke et al, , 2014Thomas and Zakharenko, 2021). Other miRNAs identified by GWAS have been implicated in schizophrenia (Yoshino and Dwivedi, 2020).…”
Section: Schizophrenia-risk Genes and Mechanisms Of Thalamic Dysfunctionmentioning
confidence: 99%
“…Idiopathic schizophrenia is also strongly linked to miRNAs. Most notably, genetic variants of MIR137, which encode miR-137, contribute to schizophrenia risk (Ripke et al, 2011(Ripke et al, , 2013(Ripke et al, , 2014Thomas and Zakharenko, 2021). Other miRNAs identified by GWAS have been implicated in schizophrenia (Yoshino and Dwivedi, 2020).…”
Section: Schizophrenia-risk Genes and Mechanisms Of Thalamic Dysfunctionmentioning
confidence: 99%
“…A meta-analysis conducted by Thomas and Zakharenko found that four miRNAs (miR-941, miR-199a-3p, miR-92a-3p, and miR-31-5p) were downregulated, and one miRNA (miR-103a-3p) was upregulated in subjects at high clinical risk of SZ patients that progressed to psychosis [ 67 ]. The prediction by TargetScan (Human) shows that these miRNAs likely target genes associated with neuronal function and plasticity.…”
Section: Role Of Mirnas In Neuropsychiatric Disordersmentioning
confidence: 99%
“…Attesting to a role in neuronal function, miR-103a-3p was used as part of a classifier function to predict cortical thinning. In patients at high clinical risk who proceeded to psychosis, higher-than-average rates of cortical thinning were found [ 67 ]. In the same study, normal levels of miR-223-3p were determined in the dlPFC of postmortem brain samples from SZ patients [ 67 ].…”
Section: Role Of Mirnas In Neuropsychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous approaches to attain results through precision medicine in psychotic disorders, including research related to the differentiation between early-onset schizophrenia and late-onset schizophrenia based on neuroimaging findings [ 24 ], molecular research related to the age of onset of schizophrenia [ 56 ], genetic research related to psychopharmacologic response [ 57 ], and research related to the etiologies of schizophrenia [ 58 ]. However, the complexity of psychotropic drug metabolism and scarce data related to late-onset psychosis still creates limitations in applying pharmacogenetics in clinical fields; vigorous pharmacogenetic tests are needed [ 59 ].…”
Section: Precision Medicine In Late-onset Psychosismentioning
confidence: 99%